Root cause analysis of rotary shouldered pin-box connection failure. (November 2015) - Citirik, Erman
Abstract: The threaded rotary shouldered connection considered in this study has been utilized in the oil and gas industry in drilling operations. A rotary shouldered pin-box connection failed during drilling operations in the field. The failure is investigated by employing numerical, analytical and experimental methodologies. The pin-box connection studied in this study is loaded by three different loads in the field. These loads are make-up torque, axial load due to dead weight of the drilling pipes and bending load due to axial misalignment in the drill-hole. The root-cause of a failure of a rotary shouldered pin-box connection requires careful examination of these three loads. This study was focused on make-up torque loading, which is one of the three loadings applied on the connection in the field during drilling operations. The main goal in this study is to accurately determine the axial pre-load force due to applied make-up torque of 57, 000 ft.lbs to the pin-box connection. Rosette type strain gages were employed to measure the axial pre-load in the connection. The calculated pre-load force in the connection due to applied make-up torque is documented in this publication. Highlights: Test methodology to determine the axial pre-load is developed. Rosette type strain gages were employed to measure the strain. The rotary shouldered connection is made-up and broken-down in the test. An approach to prevent galling of the thread is explained. The axial pre-load for 57, 000 ft.lbs of make-up torque is obtained.